Rethinking Money and Budget Lines: A Comparative Study of Secular and Islamic Economic Rationality - Luluk Latifah; Salameh alkhazaleh (Program Studi Ekonomi Syariah, FEBI UIN Datokarama Palu, 2024)
This study addresses the fundamental differences between secular and Islamic economic concepts of money and its usage, highlighting a research gap in understanding these paradigms. The objective is to analyze the concept of money from both perspectives and link it to rational Islamic solutions for achieving optimal welfare. Employing a qualitative methodology through library research, the study illustrates the application of these concepts with case examples. Findings reveal that in secular economics, money is viewed as a commodity that serves as a store of wealth and capital. In contrast, in Islamic economics, money is regarded as a public good that should facilitate productive transactions under Sharia principles. The research concludes that rationality in Islamic economics emphasizes not only utility maximization but also the maximization of social welfare, where optimal consumption occurs when the Sharia-compliant budget line intersects with the highest iso-maslahah curve. This study contributes to a deeper understanding of the differences in economic paradigms and their implications for Islamic financial policy, asserting that the Islamic economic system offers solutions based on values of blessing and social welfare. The findings encourage further exploration of the practical application of Sharia budget lines in contemporary economic decision-making.